Natural disasters damage victims’ goals and ambitions — which is why disaster relief is so important - Mo, Cecilia Hyunjung; Kosec, Katrina (2017)
September was the most active month on record for Atlantic hurricanes, with Hurricanes Harvey, Irma and Maria drenching East Texas, Florida, Puerto Rico, the U.S. Virgin Islands and many Caribbean nations. Record rainfalls caused catastrophic damage.